Most appropriate placement for people with dementia: individual experts' vs. expert groups' decisions in eight European countries. (10th October 2014) - Saks, Kai; Tiit, Ene‐Margit; Verbeek, Hilde; Raamat, Katrin; Armolik, Angelika; Leibur, Jelena; Meyer, Gabriele; Zabalegui, Adelaida; Leino‐Kilpi, Helena; Karlsson, Staffan; Soto, Maria; Tucker, Sue; et al.
Abstract Aims To investigate the extent of variability in individuals' and multidisciplinary groups' decisions about the most appropriate setting in which to support people with dementia in different European countries. Background Professionals' views of appropriate care depend on care systems, cultural background and professional discipline. It is not known to what extent decisions made by individual experts and multidisciplinary groups coincide. Design A modified nominal group approach was employed in eight countries (Estonia, Finland, France, Germany, the Netherlands, Spain, Sweden and the UK) as part of the RightTimePlaceCare Project. Methods Detailed vignettes about 14 typical case types of people with dementia were presented to experts in dementia care (n = 161) during November and December 2012. First, experts recorded their personal judgements about the most appropriate settings (home care, assisted living, care home, nursing home) in which to support each of the depicted individuals. Second, participants worked in small groups to reach joint decisions for the same vignettes. Results Considerable variation was seen in individuals' recommendations for more than half the case types. Cognitive impairment, functional dependency, living situation and caregiver burden did not differentiate between case types generating high and low degrees of consensus. Group‐based decisions were more consistent, but country‐specific patterns remained. Conclusions A multidisciplinary approach would standardize the decisions made about the care needed by people with dementia on the cusp of care home admission. The results suggest that certain individuals could be appropriately diverted from care home entry if suitable community services were available.